Sosialisasi Teknik Penyusunan Proposal Penelitian bagi Mahasiswa - Khairunnisa Khairunnisa; Khairani Sakdiah (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
The purpose of community service (PkM) in the form of this socialization activity is to provide understanding to students about the importance of knowing and understanding matters related to the preparation of research proposals. This is done so that students do not experience significant obstacles and difficulties while making the research proposal. Of course, the preparation of a research proposal is preceded by the selection and determination of a research title that must be understood by students, because the research title will direct students to be able to conduct research in accordance with scientific procedures. The title of the research was obtained through the findings of problems that occurred in the community until later the problems obtained were raised as a topic of discussion to be used as a research title for students. Then, it was also explained about the rules for writing the correct research proposal in accordance with the university rules. Participants in this socialization activity are students of the Sharia Banking Study Program Semester VI of 2024. This socialization activity was carried out face-to-face in the Sharia Banking Student Proposal Seminar room. This socialization activity was carried out by providing basic material and discussing in groups about research proposal preparation techniques which were preceded by finding various topic problems that occurred in a community environment so that they could be used as research titles.